Darrieus Water Turbine Performance Configuration of Blade - Kaprawi Sahim; Dyos Santoso; Jaini Jaini (Journal of Mechanical Science and Engineering, 2015)
Horizontal axis Darrieus water turbines, very suitable for use in river flows in the utilization of the kinetic energy. Water turbines studied in this test, is a six-blade Darrieus water turbines. Tests using three configuration of blade arrangements, with conditions rotor sink and drown half. Tests carried out in the watershed Ogan at the village Tabuan Ogan Komering Ulu of South Sumatra Histories. Research results obtained on each configuration of blade, the condition of the rotor and the rotor sink half drowned. High efficiency configuration occurs in parallel arrangement with the condition of the rotor blade sank half.